2019
DOI: 10.21608/adjg.2019.42135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Attachment Systems on Single Implant Retained Mandibular Overdenture

Abstract: Purpose: This study was conducted to evaluate bone height around ball and socket and equator attachment in mandibular overdenture retained by single implant. Material and methods: Ten completely edentulous patients were selected with ages ranging from 50-60 years. Single implant was inserted for each patient and they all received heat cured acrylic dentures. The ten patients were divided into two groups, group (I) have received ball &socket attachment, group (II) received equator attachment. In the fitting sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
0
0
Order By: Relevance
“…When comparing strain in the peri implant area under unilateral and bilateral loading there is a significant increase in strain for ball than equator with insignificant increase in strain in the posterior area.This may be attributed to the equator is low profile resilient attachment performance which is superior to that of the ball and socket attachment in the implant. This resiliency of the equator permits denture movement in every direction and distribution of stress induce lower stress on bone around implant of equator than ball abutment.The results also comes in agreement with previous studies that showed that the decrease marginal bone loss around the implant in crestal region which was usually a significant indicator of implant health (11) .…”
Section: Discussionsupporting
confidence: 92%
“…When comparing strain in the peri implant area under unilateral and bilateral loading there is a significant increase in strain for ball than equator with insignificant increase in strain in the posterior area.This may be attributed to the equator is low profile resilient attachment performance which is superior to that of the ball and socket attachment in the implant. This resiliency of the equator permits denture movement in every direction and distribution of stress induce lower stress on bone around implant of equator than ball abutment.The results also comes in agreement with previous studies that showed that the decrease marginal bone loss around the implant in crestal region which was usually a significant indicator of implant health (11) .…”
Section: Discussionsupporting
confidence: 92%
“…Sample size calculation was performed using G*Power version 3.1.9.7 (15) . Based on the results of a previous study (16) . A power analysis was designed to have adequate power to apply a two-sided statistical test to reject the null hypothesis that there is no difference between groups.…”
Section: Methodsmentioning
confidence: 99%